MENINGKATKAN HASIL BELAJAR KETERAMPILAN MEMBACA PEMAHAMAN PADA TEKS EXPLANASI DI KELAS X MIPA-1 SMA NEGERI 1 BOLA KABUPATEN SIKKA TAHUN PELAJARAN 2018/2019 - Fredialto Answaldus Fasmin (Journal on Teacher Education, 2021)
The research was carried out starting from the early reflections on the results of formative test done in thescience class of X , Kab. Sikka, NTT Province. The test results of Basic competence: to analyze a social function, text structure and language features of explanation text shows that of the total 26 students only 15.38% are able to meet the criteria for a minimum mastery by 75. Starting from these problems need to be followed up by applying the SAVI technique in learning reading comprehension . The formulation of the problems in this study are 1) Can the use of the SAVI technique increase student activity in learning to read comprehension in Class X  MIPA-2 SMA Negeri 1 Bola? (2) Can the use of the SAVI technique improve student learning outcomes in reading comprehension learning in Class XI MIPA-1 SMA Negeri 1 Bola? This type of research uses a classroom action research model designed in three cycles. Each cycle takes four stages, namely learning planning, implementing learning, observing, and reflecting. Sources of data in the study were 26 students of Class X MIPA-1 SMAN 1 Bola, consisting of 7 boys and 19 girls . In this study, the researcher is the author himself as a subject teacher and is assisted by a colleague as a collaborator. The data collection techniques used observation technique and test technique. Qualitative data from the results of observation about student activities are processed and analyzed descriptively with percentage to see trends that occur in each learning activity and are categorized into low, medium and high levels. The quantitative data from the test results were analyzed the average value to determine the achievement of the minimum completeness criteria of 75. The results of this study indicate that the use of SAVI techniques can improve learning activities and student learning outcomes in developing reading comprehension competencies . Student learning activities in cycle 1 were 54% increased to 78% in cycle 2 and 95% in cycle 3. The average student learning outcomes in cycle 1 were 71, increasing to 78 in cycle 2 and 82 in cycle 3.